Influence of Ce(IV) ions amount on the electrochemical behavior of organic-inorganic hybrid coatings in 0.1 mol L-1 NaCl solution - Da Silva, Fernando Santos [UNESP] (2019)
In this work, the influence of ceric ions (Ce(SO4)2) addition to the hydrolysis solution on the corrosion protection afforded by organic-inorganic hybrid coating obtained from tetraethoxysilane (TEOS) and 3-methacryloxy-propyl-trimethoxysilane (MPTS) to a carbon steel substrate in 0.1 mol L-1 NaCl solution was studied. Open circuit potential (EOC) and electrochemical impedance spectroscopy (EIS) experiments were carried out and showed that the protection afforded by the organic-inorganic hybrid coating was extremely dependent on the Ce4+ ions amount. These results were in close agreement with optical microscopy observation of the degrading surfaces, both procedures showing that more protective coating was produced when 500 ppm of Ce4+ ions were added to the organic-inorganic hybrid solution. The chemical state of the organic-inorganic hybrid coating investigated by X-ray photoelectron spectroscopy (XPS) indicated that the addition of Ce4+ ions enhances the polycondensation degree of the organic-inorganic hybrid coating leading to a denser siloxane (Si-O-Si) network. A strategy using laser-induced breakdown spectroscopy (LIBS) and UV-Vis spectrometry was set up in order to verify, respectively, the presence of Ce ions within the coating structure and its oxidation state. LIBS results confirmed the incorporation of Ce ions in the coating, which, according to UV-Vis measurements, are mainly in the (IV)-oxidation state.